The Influence of Self-Efficacy and Quality of Work Life on the Professional Commitment of Lecturers in Pamulang University, Indonesia - Saiful Anwar; Sri Utaminingsih; Shella Rachmawaty; Lili Nurlaili; Charlon T. Agos (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to analyze the influence of self-efficacy and quality of work life on the professional commitment of permanent lecturers at Pamulang University. This study uses a quantitative approach with data analysis techniques using Partial Least Squares-Structural Equation Modeling (PLS-SEM) and SITOREM analysis. The study population includes 1,557 permanent lecturers with the academic position of Assistant Expert, and the sample used is 320 people. The research instruments include questionnaires and expert assessment sheets for SITOREM analysis. The results show that self-efficacy has a significant effect on the professional commitment of lecturers with a coefficient value of 0.650. In addition, the quality of work life also affects the professional commitment of lecturers with a coefficient value of 0.344. The conclusion of this study shows that increasing self-efficacy and quality of work life together can strengthen the professional commitment of lecturers. The implication is that human resource management in higher education needs to be focused on strengthening the psychological factors and work environment of lecturers to improve the performance of the tridharma of higher education optimally.